Social media platforms and the shaping of the Algerian public space - for a communicative approach in daily life - - ميلود بوخنون, (International Journal of Social Communication, 2025)
This research paper aims to approach the topic of shaping public opinion through social media platforms,based on a communication perspective that focuses on monitoring individuals’ feedback in the traditional public space and its relationship to what is published in the virtual space.This is related to decision-makers in the power hierarchy and the relation to the owners of power in the hierarchy,who are directly or indirectly affected by what is being circulated on social media platforms in our daily lives.We have found that the process of transferring information occurs in two stages from the public space to the virtual space to decision-makers in the power hierarchy,which replaces the traditional communication known in the relationship between decision-makers and their subordinates.